Equity, Dignity, and Justice in Higher Education PostCOVID-19: The Case of a Public University in Namibia - Eveline O. Anyolo; Anna N. Hako; Sakaria M. Iipinge (European Scientific Journal, ESJ, 2023)
COVID-19 has disrupted teaching and learning and consequently introduced pedagogical changes into higher education institutions. Institutions of higher learning shifted from the traditional face-to-face, to online, teaching and learning mode. Most of the institutions of higher learning around the world, including the University of Namibia, had to re-think, re-imagine, re-innovate and re-design the provision of accessible, equitable and quality education. Despite unreliable internet connectivity and a lack of or unstable electricity supply in remote areas, institutions of higher learning resiliently continued to provide education for all students. Due to the aftermath of COVID-19, and forces from the 4th and 5th industrial revolutions, institutions of higher learning have adopted the blended learning approach, which is rooted mainly in social constructivism and classical liberal theory, which advocate for equal opportunities in education, irrespective of the socio-economic background of students. The aims of blended learning include providing different modes of content delivery to encourage interaction by students, promote the acquisition of knowledge and skills through physical classrooms, and the continuation of learning processes electronically. The blended teaching and learning approach demand that lecturers and students possess 21st-century skills in order to function effectively and build resilient mechanisms for a sustainable future. Through a desktop review, this paper explored practices of equity, dignity and justice in general higher education, but with the focus on a public university in Namibia, during and post-COVID-19. Notwithstanding infrastructural impediments and inadequate digital literacy skills among all parties, universities are determined to provide equitable and quality education for all.